Land acquisition policy and practice for cooperative housing scheme in Bahir Dar, Ethiopia: toward affordable housing solutions - Adigeh, Dereje Tessema; Abebe, Birhanu Girma (Frontiers in Sustainable Cities, 2024)
Bahir Dar, a city in Ethiopia, is grappling with the challenges of rapid urbanization, which has made affordable housing a critical issue for its growing population. This study specifically focuses on the urban land acquisition process for cooperative housing schemes, which serve as an essential component of Bahir Dar’s affordable housing program. This atudy aimed to examine the current practices, identify the challenges faced by housing cooperatives during land acquisition and construction, and propose strategies for improvement. The primary data for this research were collected through interviews with key informants from the Bahir Dar City administration’s land management, cooperative organizer office, housing development and management office, and housing cooperative committees. Additionally, three focus group discussion (FGD) sessions were conducted, involving 21 participants from cooperative members who had acquired residential land and from those who were waiting for allocation, including both female- and male-headed households. These discussions explored their views on the effectiveness of the cooperative housing scheme, the challenges encountered during cooperation and construction, and their recommendations for enhancement. Secondary data were also gathered through a comprehensive review of policies, regulations, research articles, reports, and relevant legal documents. The study revealed that, out of the 35,512 certified housing cooperative members since 2014, only 31,596 of them had received residential land plots. However, a relatively small fraction, i.e., less than 7,000 cooperative members, managed to partially or fully construct their homes. This indicates that the scheme has not fully achieved its intended goal and remains unaffordable for many members. The main challenges faced by cooperative members include lengthy delays in obtaining serviced land, high construction costs, and unrealistic building standards for cooperative housing units. In light of these findings, it is recommended that the Amhara National Regional State revise its housing cooperative policy to become affordable for cooperative housing members, particularly in terms of land acquisition costs and building standards.